Analysis of Drosophila segmentation network identifies a JNK pathway factor overexpressed in kidney cancer. - Liu, J.; Ghanim, M.; Xue, L.; Brown, C.D.; Iossifov, I.; Angeletti, C.; Hua, S.; Nègre, N.; Ludwig, M.; Stricker, T.; Al-Ahmadie, H.A.; Tretiakova, M.; et al. (Science, 2009)
We constructed a large-scale functional network model in Drosophila melanogaster built around two key transcription factors involved in the process of embryonic segmentation. Analysis of the model allowed the identification of a new role for the ubiquitin E3 ligase complex factor SPOP. In Drosophila, the gene encoding SPOP is a target of segmentation transcription factors. Drosophila SPOP mediates degradation of the Jun kinase phosphatase Puckered, thereby inducing tumor necrosis factor (TNF)/Eiger-dependent apoptosis. In humans, we found that SPOP plays a conserved role in TNF-mediated JNK signaling and was highly expressed in 99% of clear cell renal cell carcinomas (RCCs), the most prevalent form of kidney cancer. SPOP expression distinguished histological subtypes of RCC and facilitated identification of clear cell RCC as the primary tumor for metastatic lesions.